Crystal structures of diiodido-3-((pyridin-2-ylmethylene)amino)-2-(pyridin-3-yl)-2,3-dihydroquinazolin-4(1H)-one-cadmium(II) - Chen Honglin; Xiong Ying (Zeitschrift für Kristallographie - New Crystal Structures)
C19H13CdI2N5O, triclinic, P 1‾ $\overline{1}$ (no. 2), a = 9.0045(7) Å, b = 9.6113(8) Å, c = 13.1285(12) Å, α = 80.395(3)°, β = 79.861(3)°, γ = 80.512(3)°, V = 1091.99(16) Å3, Z = 2, R gt(F) = 0.0544, wR ref(F 2) = 0.1446, T = 273 K.